The Effect of Embossed Picture Technique on Reading Performance of Lea rners with Hearing Impairments: A Case of Kambui School for the Deaf - Munyendo, Sella; Irangi Wamocho, Franciscah (2010)
The purpose of this study was to find out the effect of embossed pictu re technique when used in teaching reading to the pupils with hearing impairment. The study was guided by Piaget’s theory of human mental de velopment. The study adopted an experimental design. The study was car ried out at Kambui School for the hearing impaired located on Githungu ri-Ruiru road in Kiambu District, Githunguri Division, Ngewa zone, 3 k ilometers off Kwa-Maiko centre. The school was chosen since it caters for all categories of pupils with hearing impairment from nursery to c lass eight. The school also admits pupils from all over the country. P upils were assigned randomly to the experimental and control groups. E ach group consisted of 9 pupils totaling 18. Data were collected from both experimental and control groups for a period of 6 weeks. Criterio n reference test (CTR) was used as a pre-test and post-test for the pu rpose of data collection. Nonparametric tests such as the Mann-Whitney test and the Wilcoxon sum of rank test were used to test the signific ant difference in performance in reading of pupils with hearing impair ment taught with embossed picture technique and those taught with "loo k and say" method. To determine if there was any significant effect of the degree of hearing loss on performance of pupils with hearing impa irment in reading, and the difference in performance of pupils of diff erent ages when taught with embossed picture technique, the Kruskal-Wa llis one-way Analysis of Variance (ANOVA) which takes care of small sa mples were used with the different degrees of hearing loss and the dif ferent ages as factors. The results showed that there is a high statis tical significant difference between pupils taught with embossed pictu re technique and those taught with the look and say method. The result s revealed that there is no significant age effect on reading performa nce of pupils with hearing impairment of different ages taught with em bossed picture technique. Finally, the study revealed that there is no significant performance difference in reading of pupils with hearing impairment at different degrees of hearing loss when taught with embos sed picture technique.